Visualization study on the condensation in a propylene loop heat pipe operating at condenser temperatures between 153 and 283 K. (25th February 2021) - Yan, Kaifen; Li, Nanxi; Zhao, Runze; Wu, Yinong; Xie, Rongjian
Abstract: A cryogenic loop heat pipe (CLHP) is an effective means of temperature control at low temperatures, but the physical properties of cryogenic working fluids are quite different from those of room-temperature working fluids, and their phase change and heat transfer characteristics need to be further studied. In this paper, a test system for evaluating the loop heat pipe (LHP) heat transfer performance and visualizing the condensation phenomenon in the condenser was fabricated. The performance of a propylene LHP with 20 W of heat exchange was tested as the condenser temperature was varied from 283 to 153 K, and the flow patterns and heat transfer characteristics during condensation were obtained. With the decreasing condenser temperature, slug flow disappeared, and pseudo-slug flow occurred and transitioned into wavy-annular flow, which was mainly caused by the increase of density ratio and viscosity ratio of the liquid to vapor. These change of flow pattern further affected the two-phase heat transfer and the performance of the CLHP. Pseudo-slug flow was observed at a condenser temperature of 273 to 203 K and it had a notable influence on the condensation pressure drop. The heat transfer coefficient of the two-phase region ranged from 2500 to 5500 W/m 2 K. When the condenser temperature ranged from 203 to 173 K, the transition of flow pattern and the fluctuation in the system caused a large deviation between the obtained and predicted heat transfer coefficients, and at other condenser temperatures, the obtained values were consistent with the predicted values for the corresponding flow patterns. Highlights: Visualization experiments in a propylene CLHP condenser were performed. The condensation flow pattern of cryogenic fluids in a CLHP was recorded and analyzed. The relationship between condensation flow pattern and CLHP performance was analyzed. Applicability of condensation HTC correlations for cryogenic fluids was discussed.